Revisiting the Madman Theory: Evaluating the Impact of Different Forms of Perceived Madness in Coercive Bargaining. (20th October 2019) - McManus, Roseanne W.
Abstract: This article reconsiders the theoretical logic behind the "Madman Theory"—the argument that it can be beneficial in coercive bargaining to be viewed as mad, or insane. I theorize about how we can best define perceived madness in a way that is relevant for analyzing coercive bargaining. I identify four types of perceived madness, broken down along two dimensions. The first dimension is whether a leader is perceived to (a) make rational calculations, but based on extreme preferences, or (b) actually deviate from rational consequence-based decision making. The second dimension is whether a leader's madness is perceived to be (a) situational or (b) dispositional. I argue that situational extreme preferences constitute the type of perceived madness that is most helpful in coercive bargaining. I illustrate my argument using case studies of Adolf Hitler, Nikita Khrushchev, Saddam Hussein, and Muammar Gaddafi.